Looking for a miracle - Brunstetter, Wanda E. (Brunstetter, Wanda E. Brides of Lancaster County, 2006)
As a child, Rebekah Stoltzfus suffered a freak accident that left her legs paralyzed. Now, confined to a wheelchair, she feels she'll never measure up to the expectations of her Pennsylvania Amish community that a woman should marry and raise a family. She longs to be loved, yet she prays for a way to be self-supporting. Daniel Beachy wants to court Rebekah, but she believes that she is a burden and has convinced herself that love is not for her. Will Rebekah's search for a miracle come true? Or, will she miss God's gift in her battle between self-pity and the determination to be independent?